(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
Malaria is one of the most common infectious diseases and an enormous public health problem. According to the World Malaria report 2008, about 247 million malaria cases were present worldwide among 3.3 billion people at risk in 2006, causing nearly a million deaths. This autopsy based retrospective study was carried out at Kasturba Medical College, Mangalore. Autopsy records of the cases autopsied during September 2004 to August 2008 were reviewed and cases confirmed of malaria after histopathological examination were included in the study. Out of 2515 cases autopsied during the study period, sudden death was reported in 274 cases, out of which five cases were confirmed as of sudden death due to malaria. The histopathology examination revealed infiltration of acute and chronic inflammatory cells with numerous parasitized RBCs containing malarial pigment in the visceral organs. Fatality due to malaria is seen even with good diagnostic facilities and treatment, especially in developing countries like India. Importance of complete autopsy and histopathological examination in identifying malaria related mortality is stressed.